Youth Generation Moral Education in Muhammadiyah University of Enrekang - Saldi Saldi; Selfie Ulansari; Rahmahdhani . J.N; Elihami Elihami (Universitas Muhammadiyah Enrekang, 2022)
Morals are good behavior that appears from a person after carrying out Islamic law, so that these morals and customs are formed into behaviors and traits that are firmly embedded in the self, so that when carrying out an act without requiring prior consideration. Morals occupy a special position in Islam, namely they are positioned together with the essence of ihsan, so that aqidah and shari'a will not be perfect without morals because all three are an inseparable unit. So the higher a person's Iman, the better his morals. One of the factors of moral decline is caused by internal factors, namely